Ab Initio Molecular Dynamics Study of the Structure and Properties of Nb-Doped Zr-Cu-Al Amorphous Alloys - Hongqing Wei (MDPI AG, 2021)
In this paper, experiments were carried out on (Zr0.5Cu0.4Al0.1)100-xNbx (x = 0, 3, 6 at.%) amorphous alloys, and the corresponding ab initio molecular dynamics simulation was performed. The results showed that stable structures of Nb-centered and Al-centered icosahedral (-like) atomic clusters were formed after a small amount of (3 at.%) Nb was added. Stable and close-packed backbone structures were formed by the means of interconnection and matching of the two kinds of stable clusters in the alloys, which also enhanced the overall heterogeneity of the structures, thereby improving the strength and macroscopic plasticity. In addition, when more (6 at.%) Nb was added, the stable Al-centered clusters were replaced by some stable Nb-centered clusters in the alloys, and the stability and heterogeneity of the structures were partly reduced, which reduced the strength and macroscopic plasticity.